The role of Lymphocytes Apoptosis in Grave’s Disease Patients - Al-Samaraee, Israa F. J.; Salih, Saba F.; Idrees Khattab, Y’arub (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Apoptosis is a physiological type of cell death; it is active, well-controlled genetic program of cell death that does not produce inflammatory process. It is involved in cell turnover in healthy adult tissues and it is responsible for focal elimination of unwanted cells during normal embryonic development, organ homeostasis, immune regulation and defense without causing stress to the neighboring cells. Method: This study was carried on 30 Grave’s disease female patients with a mean age of (29.8 ± 8.3) years. The study parameters were considered as: before and after treatment; patient becomes clinically and biochemically euthyroid after 4-6 weeks of starting treatment with antithyroid drug (carbimazole).From each patient 7 mL of blood were aspirated (2ml for detection of peripheral blood lymphocyte apoptosis 5ml for T3,T4andTSH).For each patient fine needle aspirate (FNA) from thyroid tissue to study the histopathological changes by Hematoxylene and eosin stain, and lymphocyte apoptosis by DNA binding dye Acridine orange. Results: The percentage of peripheral blood lymphocytes apoptosis increased significantly after treatment (23.9 ± 5.06) than its percentage before treatment (11.1 ± 1.8) with P value < 0.00001, as detected by DNA-binding fluorescent stain (acridine orange). There was a significant increase of intrathyroidal lymphocytes apoptosis (21.7±4.2) and (34.7±5.6) before and after treatment respectively with a P value < 0.0001, detected by acredine orange and hematoxylin and eosin stains. T3, T4 and thyroid autoantibody levels decreased significantly, while TSH level increase significantly after treatment. Conclusion: Grave’s disease is associated with increased rate of apoptosis in both peripheral blood lymphocytes and intrathyroidal lymphocytes. After treatment with carbimazole there was significant Increase in peripheral blood lymphocytes and intrathyroidal lymphocytes apoptosis, this lead to significant decrease in the autoimmune reaction assessed by decrease in the anti thyroglobulin antibodies in serum.